2016
DOI: 10.1002/nau.22809
|View full text |Cite
|
Sign up to set email alerts
|

Do we need to know more about the effects of hormones on lower urinary tract dysfunction? ICI-RS 2014

Abstract: This review article reflects the presentations and subsequent discussions during a think tank at the 5th International Consultation on Incontinence Research Society’s annual meeting, held in Bristol, UK (September 22–24, 2014). It reviews the current state of knowledge on the role of hormones in lower urinary tract dysfunction (LUTD) and overactive bladder (OAB) and in particular: highlights some specific basic research findings from discussion participants; reviews future research topics; and discusses potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 60 publications
0
30
0
1
Order By: Relevance
“…In the 2002 standardization document, low estrogen and menopause are recognized as a cause of nocturia, and androgen deprivation is also associated with LUTS and nocturia. There is no evidence‐based medicine to demonstrate that hormonal substitution in postmenopausal women is an effective treatment of nocturia (ICI‐RS 2017) . The 2015 NICE guidelines (https://www.nice.org.uk/guidance/ng23) state that there is a good evidence that hormonal substitution is helpful for vasomotor symptoms (hot flushes) and for vaginal atrophy and its consequences, but do not mention nocturia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 2002 standardization document, low estrogen and menopause are recognized as a cause of nocturia, and androgen deprivation is also associated with LUTS and nocturia. There is no evidence‐based medicine to demonstrate that hormonal substitution in postmenopausal women is an effective treatment of nocturia (ICI‐RS 2017) . The 2015 NICE guidelines (https://www.nice.org.uk/guidance/ng23) state that there is a good evidence that hormonal substitution is helpful for vasomotor symptoms (hot flushes) and for vaginal atrophy and its consequences, but do not mention nocturia.…”
Section: Resultsmentioning
confidence: 99%
“…The sex hormones are also involved in regulation of diuresis. 26 Deficiency in sex hormones (estrogen, testosterone) is diagnosed based on history taking and physical examination and can be confirmed with blood analysis. Some validated questionnaires are available for diagnosing menopause.…”
Section: Hormones and Nocturiamentioning
confidence: 99%
“…, ; Hanna‐Mitchell et al. ). Large epidemiological studies investigating the use of systemic hormone replacement therapy in the prevention of cardiovascular disease and osteoporosis revealed that these therapies may increase the risk for development of urinary incontinence (Grady et al.…”
Section: Introductionmentioning
confidence: 99%
“…As BK channels are fundamental regulators of DSM function under normal and OAB conditions, when the channel expression is altered, pharmacological modulation of their activity could potentially be an effective approach to treat forms of lower urinary tract dysfunction, such as OAB (Petkov , ; Hanna‐Mitchell et al. ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation